The unabated power of South African traditional leaders on service delivery enhancement - Kgobe, F. K. L.; Makalela, K.I. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
This paper evaluates the powers, functions, responsibilities and the potency of traditional leaders in relation to service delivery enhancement in the South African ambit. The concerted roles and responsibilities of traditional leaders has remained a controversial issue in the democratic dispensation. This paper posits and postulates that there is still a continuing dialectical and unequivocally clash between forces of modernity for development and governance in relation to the persistent strength of traditional leaders. Over and above, service delivery is still an alarming issue affecting almost all South African municipalities. Therefore, this paper habitually argues that the integration and unsurpassed concerted amid of traditional leaders can palpably ameliorate service delivery in their areas of jurisdiction. The latter is diametrically attributed to the fact that the Constitution of the Republic of South Africa, 1996 recognizes traditional leaders and made provision for them to deliberate on matters affecting the local government although that is not clearly defined. However, section 151 of the Constitution defines the powers and functions of elected councilors which largely overlaps with those exercised by traditional leaders. This paper is purely conceptual which relied heavily on documents and literature review to fortify the argument and accentuate the amid power of traditional leaders and service delivery enhancement. The conclusion that can be drawn from this paper is that there is a need for an amicable and collaborative exertion between the traditional leaders, communities and the local government for effective service delivery. As a remedy, the paper recommends that there is a need for central government to clarify the terms of reference for traditional leadership at local level.
Journal article published in the 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Constitution; Democracy; Developmental Local Government; Service Delivery; Local governmenent -- South Africa; Municipal government -- South Africa